The Effect of Financial Report Transparency and Zakat Management on Muzakki Trust in BAZNAS Lombok Timur - Munir, Zainal Arifin Haji (Al-Risalah, 2021)
This study aims to analyze the effect of variable transparency of financial reports and zakat management at the National Amil Zakat Agency (BAZNAS) Lombok Timur on Muzakki trusts. As a non-profit organization, BAZNAS needs to pay attention to the satisfaction of the Muzakki, transparency and accountability of their institution to be able to increase Muzakki loyalty. The sample in this study is people who pay zakat (Muzakki) through BAZNAS. The Number of Samples used in this study amounted to 93 respondents, the data source was observations, questionnaires and documentations. The analysis of the data used IBM SPSS Statistics version 26. Analysis was carried out by several tests, success as validity test, reliability test, normality test, heteroscedasticity test, linearity test, linear regression analysis and coefficient of determination test. The results of this study indicate that the zakat management variable has a significance value of 0.014 <0.05 and a tcount value of 2.515> 1.98667, which means that the zakat management variable affects the trust of Muzakki. The transparency of financial statements has a positive and significant effect on Muzakki's trust, so the second hypothesis in this study is accepted. The results of this study indicate that the financial statement transparency variable has a significance value of 0.000 <0.05 and a tcount value of 5.208> 1.98667, which means that the financial statement transparency variable has an effect on Muzakki's trust. Zakat management and transparency of financial statements simultaneously affect the trust of Muzakki. So that the third hypothesis in this study is accepted. The results of this study indicate that the zakat management variable has a significance value of 0.000 <0.05 and an Fcount of 66,000> 3.10. So, it can be concluded that the variables of zakat management and financial statement transparency have a simultaneous effect on Muzakki's trust.